2014
DOI: 10.1142/s0217984914300142
|View full text |Cite
|
Sign up to set email alerts
|

A brief review of Badger–Bauer rule and its validation from a first-principles approach

Abstract: Understanding the acid-base interactions is important in chemistry, biology and material science as it helps to rationalize materials properties such as interfacial properties, wetting, adhesion and adsorption. Quantitative relation between changes in enthalpy (ΔH) and frequency shift (Δν) during the acid-base complexation is particularly important. We investigate ΔH and Δν of twenty-five complexes of acids (methanol, ethanol, propanol, butanol and phenol) with bases (benzene, pyridine, DMSO, Et 2 O and THF) i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 53 publications
0
16
0
1
Order By: Relevance
“…The qualitative correlation between H‐bond strengths and stretching frequencies has been observed in many chemical systems . Although a single linear relationship does not hold throughout the many diverse types of H‐bonding, satisfactory linear correlations between enthalpy of H‐bond formation, the IR stretching frequency shift, and the X–H bond elongation were found for structurally related compounds …”
Section: Spectroscopic Signatures Of Hyperconjugationmentioning
confidence: 99%
“…The qualitative correlation between H‐bond strengths and stretching frequencies has been observed in many chemical systems . Although a single linear relationship does not hold throughout the many diverse types of H‐bonding, satisfactory linear correlations between enthalpy of H‐bond formation, the IR stretching frequency shift, and the X–H bond elongation were found for structurally related compounds …”
Section: Spectroscopic Signatures Of Hyperconjugationmentioning
confidence: 99%
“…Acid–base interactions are fundamental chemical phenomena that can control the visible colors of organic molecules through the absorption and emission of light. Halochromic and halofluoric properties have a wide range of applications in chemosensors and organic electronic devices .…”
Section: Methodsmentioning
confidence: 99%
“…Acid-base interactions [1] are fundamental chemical phenomena that can control the visible colors of organic molecules through the absorption and emission of light.H alochromic and halofluoric [2] properties have aw ide range of applications in chemosensors and organic electronic devices. [3] Nitrogencontaining functional groups such as pyridyl, [4] pyrazinyl, [5] pyrimidyl, [6] alkylamino, [7] and indolizyl moieties [8] in chromophores can be protonated, and the resulting speciesu sually exhibit pH-dependentb athochromic shifts of their absorption and emission spectra.I na ddition to the halofluorism inducedb y Brønsteda cids, that triggered by Lewis acids is also of great interest.…”
mentioning
confidence: 99%
“…Of these, perhaps the earliest is the Badger–Bauer rule that correlates the redshift in the donor stretching frequency with the enthalpy of hydrogen‐bond formation . Examples that follow the Badger–Bauer rule have been reported in the literature …”
Section: Introductionmentioning
confidence: 93%
“…[16] Examples that follow the Badger-Bauer rule have been reported in the literature. [17][18][19][20][21] In ar ecent report, our group demonstrated that for as eries of CÀH···X (X = O, N) hydrogen-bonded complexes of 3-fluoro-phenylacetylene and 2,6-difluorophenylacetylene the redshifts in the CÀHs tretchingf requency weren ot linearly correlated with the stabilization energies. [22] Analysis of the frequency shifts with the aid of symmetry-adaptedp erturbation theory (SAPT), which separates the total interaction energy into physically well-defined components, such as electrostatics, induction, dispersion, and exchange repulsion, suggested that the redshifts in the donors tretchingf requency are linearly proportional tot he electrostaticc omponent of the total stabilization energy.S imilar results were reported for the water complexes of various substituted phenolsi nvestigated by using matrixisolation spectroscopy.…”
Section: Introductionmentioning
confidence: 99%